Similarities in the computed tomography appearance in α1-antitrypsin deficiency and smoking-related chronic obstructive pulmonary disease in a smoking collective - Konietzke, Philip; Jobst, Bertram; Wagner, Willi Linus; Kauczor, Hans-Ulrich; Wielpütz, Mark Oliver (Respiration, 2018)
Emphysematous destruction of lung parenchyma visible in computed tomography (CT) can be attributed to chronic obstructive pulmonary disease (COPD) or to α1-antitrypsin deficiency (AATD). We evaluated if visual semiquantitative phenotyping of CT data helps identifying individuals with AATD in a group of smokers with severe emphysema and airflow limitation.